Associations Between Sedentary Lifestyle, Cardiorespiratory Fitness, and Physiological Responses Among Adolescents: A Systematic Literature Review: Inggris - M. Alfath; Wawan Junresti Daya; Tri Bayu Norito; Ilham; Boy Indrayana (Athena: Physical Education and Sports Journal, 2026)
Sedentary lifestyle has become an increasingly important health concern among adolescents, largely due to insufficient physical activity and the widespread use of digital devices. This behavior is believed to be associated with reduced cardiorespiratory fitness and adverse physiological responses. Therefore, this study aimed to examine the relationship between sedentary lifestyle, cardiorespiratory fitness, and physiological responses among adolescents through a Systematic Literature Review (SLR). The review was conducted following the PRISMA 2020 guidelines. Relevant studies published between 2015 and 2025 were identified through searches of the Scopus and Google Scholar databases. Of the 190 records initially retrieved, 10 primary studies met the inclusion criteria and were included in the final analysis. Data were synthesized using a narrative synthesis approach. The findings indicated that higher levels of sedentary behavior and prolonged screen time were consistently associated with lower cardiorespiratory fitness, reduced aerobic capacity as reflected by lower VO₂max values, and unfavorable physiological outcomes, including elevated blood pressure and resting heart rate. In contrast, regular participation in physical activity was associated with better cardiorespiratory and physiological health. Furthermore, school-based physical activity programs were found to contribute to reducing sedentary behavior among adolescents. Overall, the evidence suggests that sedentary lifestyle is associated with diminished cardiorespiratory fitness and negative physiological changes in adolescent populations.